Computed tomography-based angiographic evaluation of circle of willis and its variations. First documented evidence from Northern India - Shah Sumaya Jan; Bashir Ahmad Shah; Shabir Ahmad Bhat; Syed Shah Faisal; Sheikh Mohd Saleem (Current Medical Issues, 2022)
Background: The circle of Willis (CW) encircles the pituitary stalk and is considered an anastomotic vascular system that links the forebrain and hindbrain. Because morphology varies between races, it was reasonable to do research on the anatomy of the CW. The purpose of this study was to determine the anatomical variations in the arteries composing the CW on computed tomography (CT angiography) in the adult Kashmiri population. Materials and Methods: This was a cross-sectional descriptive study conducted to assess the structural characteristics of CW and to estimate the prevalence of anatomical variations of CW in the adult Kashmiri population among those who were permanent residents of Kashmir Valley, aged 20 years or older, and who were referred for CT angiography from the Department of Medicine or Surgery with the diagnosis of CW. Results: A total of 50 (23.1%) studied CT angiography were having the presence of any anatomical variations, while 166 (76.9%) had normal anatomical origins. Arteries forming the CW (polygon) were found to be absent among 9 (4.16%) and 5 (2.3%) had fetal origin of arteries forming the CW. Trifurcation of arteries was found among only 2 (0.9%), hypoplastic arteries were found among 34 (15.7%), and complete circles were present in 207 (95.8%) CT angiographs. Right and left internal carotid artery, right and left anterior cerebral artery, the right middle and left middle cerebral artery, and the anterior communicating artery were all present. Conclusion: Hypoplasia was more prevalent in a posterior circle, absent arteries in the anterior circulation, while accessory vessels were common in the anterior portion of the circle.